FeM-N core-shell type catalyst as well as preparation method and application thereof

By developing FeM@N core-shell catalysts, using inorganic membranes to control the catalyst particle size and protect the active site, the high energy consumption and inconvenient operation of chemical exothermic reactions in heavy oil thermal production are solved, efficient synthesis gas conversion and controllable product distribution are achieved, and a wide range of industrial application prospects are achieved.

CN119524915APending Publication Date: 2025-02-28CNOOC INST OF CHEM & NEW MATERIALS (BEIJING) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411700048.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize chemical exothermic reactions in heavy oil thermal production, which has problems such as high energy consumption, inconvenient operation and safety hazards. At the same time, the cost of metal nanocrystalline viscosity reducing agents is high and difficult to produce on a large scale.

Method used

A FeM@N core-shell catalyst was developed to control the particle size of the iron-based catalyst and protect the catalytic active site by introducing a specific inorganic membrane as the shell layer to achieve efficient exothermic reaction in a high temperature and high pressure environment.

Benefits of technology

It achieves efficient synthesis gas conversion rate and controllable product distribution in heavy oil thermal production, reduces energy consumption, improves the long-term operation capacity of the catalyst, and has broad prospects for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a FeM-N core-shell type catalyst and a preparation method and application thereof and relates to the technical field of petrochemical engineering, the FeM-N core-shell type catalyst comprises an iron-based catalyst serving as a core and an inorganic membrane serving as a shell layer, and the preparation method comprises the following steps that firstly, a metal precursor solution is subjected to a co-precipitation reaction in an alkaline environment, and a metal precursor solution is obtained; the preparation method comprises the following steps: preparing an iron-based metal core catalyst, performing in-situ coating on the iron-based metal core catalyst with an inorganic membrane with mesopores and / or micropores as a shell layer, and performing aging and crystallization to obtain the FeM-N core-shell type catalyst, according to the method, the FeM (at) N core-shell type catalyst with a controllable structure and capable of generating hydrocarbon and releasing heat can be obtained by adjusting the concentration and coating times of the inorganic membrane precursor. The FeM-N core-shell type catalyst can be used for thermal recovery of thickened oil to improve the recovery rate, and the temperature of an oil layer is increased through hydrocarbon generation and heat release, so that the viscosity of the thickened oil can be greatly reduced, and the purpose of effectively improving the recovery rate of the thickened oil is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of petrochemical industry, and in particular to a FeM@N core-shell catalyst and a preparation method and application thereof. Background Art

[0002] Heavy oil production is an important part of ensuring stable crude oil production. The continuous and efficient development of heavy oil resources is of great practical significance for ensuring national energy security. Since heavy oil thermal recovery will release a large amount of CO2, under the current "dual carbon" background, heavy oil development urgently needs to develop in the direction of low emissions and low energy consumption.

[0003] Prior art CN114737937A discloses a method for controlling reaction heat during heavy oil in-situ exothermic reaction recovery. This method continuously injects hot water vapor and reaction raw gas containing H2 and CO into the underground through an injection well, and uses Fischer-Tropsch oil or white oil as a carrier liquid to carry an exothermic catalyst into the underground oil layer. An exothermic reaction occurs in the underground oil layer to reduce the amount of hot water vapor used in the heavy oil thermal recovery process, while reducing the viscosity of the heavy oil and improving the recovery rate of the heavy oil.

[0004] Prior art CN114876429A discloses a method for exploiting heavy oil reservoirs by utilizing wellbore catalytic heat generation, which mainly includes an injection well and a production well. Steam and a non-condensable gas mixture containing carbon, hydrogen and oxygen elements are injected into the annular space of the oil pipe and the casing by means of tubing injection and casing production. Under a certain pressure, the high-temperature steam, light hydrocarbons and residual gas that has not been completely reacted generated at the bottom of the well are injected into the heavy oil reservoir.

[0005] Prior art CN114658403A discloses an experimental device and method for simulating the effects of multidimensional chemical reactions in porous media. The device comprises an injection unit, a model unit, an output unit and an electric heating unit. The model unit is used to simulate the effects of multidimensional chemical reactions in porous media, and the electric heating unit is used to cause multidimensional chemical catalysts to react chemically, and the heat generated is used for oil recovery. Although the device can make full use of the heat released by the chemical reaction, reduce external heat input, and achieve the effect of improving oil recovery efficiency, there are problems such as high energy consumption of the electric heating unit, inconvenient operation, and potential safety hazards.

[0006] Prior art CN107880866A discloses a metal nanocrystal viscosity reducer for in-situ catalytic reduction of heavy oil. The metal nanocrystal viscosity reducer is prepared by a liquid phase reduction method, and has the advantages of simple and controllable preparation method, uniform particle size, obvious viscosity reduction effect, and a viscosity reduction rate of up to 93.3%. However, the metal nickel nanocrystal uses an organic amine as a precursor, which has the problems of high cost and difficulty in large-scale production.

[0007] Based on the status of the above existing technologies, if the heat released and the hydrocarbons produced by exothermic reactions in chemical industry can be utilized, it will provide new possibilities for the low-carbon development of heavy oil thermal recovery. The reaction refers to the process of generating hydrocarbons using synthesis gas (CO and H2) as raw materials under suitable catalysts and reaction conditions. The carbon number distribution of hydrocarbons can be controlled by reaction conditions and catalyst parameters. How to develop catalysts with simple preparation methods, controllable product selectivity and adjustable heat is the key to the reaction in complex wellbores.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] One of the purposes of the present invention is to provide a FeM@N core-shell catalyst that can be used to simulate the exothermic reaction under high temperature and high pressure environment in underground heavy oil layers, which not only has a high synthesis gas conversion rate, but also has controllable product distribution and heat release.

[0010] The second object of the present invention is to provide a method for preparing a FeM@N core-shell catalyst, which can prepare a core-shell catalyst with controllable structure and film thickness, has a simple process, and has broad prospects for industrial production.

[0011] The third object of the present invention is to provide an application of a FeM@N core-shell catalyst, which is beneficial to the green and low-carbon exploitation of heavy oil by utilizing the heat released by chemical reactions and the generation of hydrocarbons.

[0012] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0013] In a first aspect, a FeM@N core-shell catalyst comprises an iron-based catalyst as a core and an inorganic membrane as a shell layer;

[0014] The inorganic membrane has a mesoporous and / or microporous structure;

[0015] The inorganic film includes at least one of SiO2, ZSM-5, β and Silicalite-1.

[0016] Further, the particle size of the iron-based catalyst as the core is 20nm-2000nm, preferably 50nm-1000nm;

[0017] The thickness of the inorganic film as the shell layer is 1 nm-500 nm, preferably 20 nm-200 nm.

[0018] In a second aspect, a method for preparing the FeM@N core-shell catalyst described in any one of the above items comprises the following steps:

[0019] (a) subjecting a metal precursor solution to a coprecipitation reaction in an alkaline environment to obtain a precipitate, and calcining the precipitate to obtain a catalyst containing an iron-based metal;

[0020] (b) In-situ coating of the iron-based metal catalyst by an inorganic membrane, followed by aging and crystallization, to obtain the FeM@N core-shell catalyst.

[0021] Furthermore, the metal precursor includes an iron salt and a metal additive;

[0022] The iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide;

[0023] The metal additive includes at least one of Zr salt, Mn salt, Ce salt, Zn salt, K salt, Na salt and La salt;

[0024] The molar ratio of the iron salt to the metal additive is 1:(0.01-5), preferably 1:(0.1-1).

[0025] Further, the molar concentration of the metal precursor solution is 0.1 mol / L to 10 mol / L, preferably 0.5 mol / L to 2 mol / L;

[0026] The molar concentration of the alkaline solution in the alkaline environment is 0.1 mol / L to 10 mol / L, preferably 0.5 mol / L to 2 mol / L.

[0027] Further, the coprecipitation reaction temperature is 50°C to 120°C, preferably 70°C to 90°C;

[0028] The pH condition of the coprecipitation reaction is 7-12, preferably 7.5-10.

[0029] Further, the roasting method includes roasting in air;

[0030] The calcination temperature is 300°C to 600°C, preferably 400°C to 500°C;

[0031] The calcination time is 10 h to 24 h, preferably 15 h to 18 h.

[0032] Furthermore, the in-situ coating method includes at least one of a sol-gel method, a hydrothermal synthesis method and a physical coating method.

[0033] Further, the aging temperature is 25°C to 100°C, preferably 30°C to 60°C;

[0034] The crystallization temperature is 60°C to 240°C, preferably 130°C to 180°C;

[0035] The method further comprises the step of calcining the obtained product in air after the crystallization.

[0036] In a third aspect, a FeM@N core-shell catalyst as described in any one of the above items is used in in-situ hydrocarbon generation and heat release during thermal recovery of heavy oil.

[0037] Compared with the prior art, the present invention has at least the following beneficial effects:

[0038] The FeM@N core-shell catalyst provided by the present invention can effectively control the particle size of the iron-based catalyst by introducing a specific inorganic membrane as a shell layer, and can also protect the catalytic active sites from being contaminated by water and oil in the wellbore. On the other hand, it can effectively prevent the iron-based catalytic active particles from becoming larger during the reaction exothermic process, so as to stabilize (extend) the catalytic activity, thereby ensuring the long-term operation of the catalyst. In short, the FeM@N core-shell catalyst with hydrocarbon generation exothermic effect of the present invention is suitable for simulating exothermic reactions under high temperature and high pressure environment in underground heavy oil layers, and not only has a high synthesis gas conversion rate, but also has controllable product distribution and heat release.

[0039] The preparation method of the FeM@N core-shell catalyst provided by the present invention can prepare a core-shell catalyst with controllable structure and film thickness. The preparation method is simple to operate and has broad prospects for industrial production.

[0040] The application of the FeM@N core-shell catalyst provided by the present invention can regulate the reaction rate, the degree of heat release and the distribution of hydrocarbon products by adjusting the active center of the catalyst and controlling the reaction conditions, which is beneficial to the green and low-carbon mining of heavy oil by utilizing the heat released by chemical reactions and the generation of hydrocarbons, and is beneficial to the integrated development of upstream and downstream industries. DETAILED DESCRIPTION

[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] According to a first aspect of the present invention, there is provided a FeM@N core-shell catalyst, comprising an iron-based catalyst as a core, and an inorganic membrane as a shell layer;

[0043] The inorganic membrane has a mesoporous and / or microporous structure, and the inorganic membrane includes at least one of SiO2, ZSM-5, β and Silicalite-1.

[0044] The FeM@N core-shell catalyst provided by the present invention can effectively control the particle size of the iron-based catalyst by introducing a specific inorganic membrane as a shell layer, and can also protect the catalytic active sites from being contaminated by water and oil in the wellbore. On the other hand, it can effectively prevent the iron-based catalytic active particles from becoming larger during the reaction exothermic process, so as to stabilize (extend) the catalytic activity, thereby ensuring the long-term operation of the catalyst. In short, the FeM@N core-shell catalyst with hydrocarbon generation exothermic effect of the present invention is suitable for simulating exothermic reactions under high temperature and high pressure environment in underground heavy oil layers, and not only has a high synthesis gas conversion rate, but also has controllable product distribution and heat release.

[0045] It should be noted that in the FeM@N core-shell catalyst, the raw gas (CO and H2) first passes through the inorganic membrane to reach the surface of the iron-based catalyst for hydrogenation reaction, and the intermediate products generated then diffuse to the surface of the inorganic membrane, and further dehydrogenation reaction, polymerization reaction and carbon-carbon growth reaction occur on the surface and pores of the inorganic membrane, and the final product is desorbed from the molecular sieve; the core-shell structure of the catalyst can ensure that the intermediate products have an equal opportunity to contact the membrane for subsequent reactions, ensuring that the cascade reaction occurs in an orderly manner, thereby promoting the directional conversion of the raw gas and intermediate products into target products.

[0046] In a preferred embodiment, the particle size of the iron-based catalyst as the core may be 20nm-2000nm, and may further preferably be 50nm-1000nm. Typical but non-limiting particle sizes are, for example, 50nm, 100nm, 200nm, 500nm, 800nm, and 1000nm.

[0047] In a preferred embodiment, the thickness of the inorganic film as the shell layer may be 1 nm-500 nm, and may further preferably be 20 nm-200 nm. Typical but non-limiting thicknesses include 20 nm, 30 nm, 50 nm, 100 nm, 150 nm, and 200 nm.

[0048] According to a second aspect of the present invention, there is provided a method for preparing the FeM@N core-shell catalyst described in any one of the above, comprising the following steps:

[0049] (a) subjecting a metal precursor solution to a coprecipitation reaction in an alkaline environment to obtain a precipitate, and calcining the precipitate to obtain a catalyst containing an iron-based metal;

[0050] (b) The Fe-based metal catalyst is in situ coated with an inorganic membrane, and then aged and crystallized to obtain a FeM@N core-shell catalyst.

[0051] The preparation method of the FeM@N core-shell catalyst provided by the present invention can prepare a core-shell catalyst with controllable structure and film thickness. The preparation method is simple to operate and has broad prospects for industrial production.

[0052] In a preferred embodiment, the metal precursor can be a mixture of an iron salt and a metal additive; wherein the iron salt includes but is not limited to at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide; the metal additive includes but is not limited to at least one of Zr salt, Mn salt, Ce salt, Zn salt, K salt, Na salt and La salt.

[0053] In the present invention, the molar ratio of iron salt to metal additive can be 1:(0.01-5), and can be further preferably 1:(0.1-1). Typical but non-limiting molar ratios are, for example, 1:0.01, 1:0.1, 1:0.5, 1:1, 1:1.2, 1:1.5, 1:1.7, and 1:2.

[0054] In a preferred embodiment, the molar concentration of the metal precursor solution can be 0.1mol / L to 10mol / L, and can be further preferably 0.5mol / L to 2mol / L. Its typical but non-limiting molar concentration is, for example, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.5mol / L, and 2.0mol / L.

[0055] In a preferred embodiment, the molar concentration of the alkali solution in the alkaline environment can be 0.1mol / L to 10mol / L, and can be further preferably 0.5mol / L to 2mol / L. Its typical but non-limiting molar concentration is, for example, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.5mol / L, and 2.0mol / L.

[0056] In a preferred embodiment, the temperature of the coprecipitation reaction can be 50°C to 120°C, and can be further preferably 70°C to 90°C, and typical but non-limiting temperatures are, for example, 70°C, 75°C, 80°C, 85°C, and 90°C; the pH condition of the coprecipitation reaction can be 7 to 12, and can be further preferably 7.5 to 10, and typical but non-limiting pH conditions are, for example, 7.5, 8, 8.5, 9, 9.5, and 10.

[0057] In the present invention, the precipitate obtained by the coprecipitation reaction can be washed with deionized water, and the liquid-solid ratio of the washing can be 50% to 80%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, but not limited to this; the precipitate can be washed 3 to 5 times until the washing liquid is neutral.

[0058] The method of calcining the precipitate includes but is not limited to calcining in air. The calcination temperature can be 300°C to 600°C, and can be further preferably 400°C to 500°C. Typical but non-limiting temperatures are, for example, 400°C, 420°C, 440°C, 460°C, 480°C, and 500°C. The calcination time can be 10h to 24h, and can be further preferably 15h to 18h. Typical but non-limiting times are, for example, 15h, 16h, 17h, and 18h.

[0059] In the present invention, the number of in-situ coating can be 1 to 10 times, and can be further preferably 1 to 5 times, for example, 1 time, 2 times, 3 times, 4 times, 5 times, but not limited to these; the mass ratio of the inorganic membrane precursor to the core catalyst can be (1 to 1000):1, and can be further preferably (1 to 100):1.

[0060] The present invention can obtain a FeM@N core-shell catalyst with controllable structure and heat release for hydrocarbon generation by adjusting the concentration of the inorganic film precursor and the number of coating times.

[0061] The in-situ coating method can be at least one of a sol-gel method, a hydrothermal synthesis method and a physical coating method; wherein the sol-gel method includes a silicon source, a template, a surfactant and a solvent, and the molar ratio thereof can be 1: 0.1-0.8: 0.01-0.1: 10-60; the hydrothermal synthesis method includes a silicon source, an aluminum source, a template and a solvent, and the molar ratio thereof can be 1: 0.01-0.1: 0.1-0.8: 10-60; the physical coating method includes an iron-based oxide, an inorganic film powder and a solvent, and the molar ratio thereof can be 1: 0.1-5: 0.1-5, and can be further preferably 1: 0.5-2: 0.5-2.

[0062] In the present invention, the template includes but is not limited to at least one of mesoporous KIT-6, carbon black, tetrapropylammonium hydroxide, polyvinylpyrrolidone, ethylamine, triethylamine, diethylamine and triethanolamine; the surfactant includes but is not limited to at least one of hexadecyltrimethylammonium bromide, dodecyldimethylphenoxyethylammonium bromide and hexadecylpyridinium chloride.

[0063] In the present invention, the silicon source includes but is not limited to at least one of silica sol, silicon powder, ethyl orthosilicate and methyl orthosilicate; the aluminum source includes but is not limited to at least one of aluminum sol, aluminum nitrate and aluminum oxide powder; the solvent includes but is not limited to at least one of deionized water, ethanol and propanol.

[0064] In a preferred embodiment, the aging temperature can be 25°C to 100°C, and can be further preferably 30°C to 60°C. Typical but non-limiting temperatures are, for example, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, and 60°C.

[0065] In a preferred embodiment, the crystallization temperature can be 60°C to 240°C, and can be further preferably 130°C to 180°C. Typical but non-limiting temperatures include 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, and 240°C.

[0066] In the present invention, after the crystallization, the step of calcining the obtained product in air is further included.

[0067] The composition (mass fraction) of the catalyst obtained by the preparation method of the present invention can be: Fe2O3 5% to 50%; ZnO 5% to 50%; MnO2 5% to 50%; CeO2 5% to 50%; SiO2 5% to 50%; ZSM-5 5% to 50%; β 5%-50%; Silicalite-1 5% to 50%; for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, but not limited to this.

[0068] According to a third aspect of the present invention, there is provided a use of any of the above-mentioned FeM@N core-shell catalysts in in-situ hydrocarbon generation and heat release during thermal recovery of heavy oil.

[0069] The FeM@N core-shell catalyst is passed through an underground in-situ modification physical simulation experimental device, with raw gas containing CO and H2 introduced. The temperature of the oil layer is heated by utilizing the heat-releasing characteristics of the catalyst chemical reaction to generate hydrocarbons, which can significantly reduce the viscosity of the heavy oil and thus increase the recovery rate of the heavy oil.

[0070] The application of the FeM@N core-shell catalyst provided by the present invention can regulate the reaction rate, the degree of heat release and the distribution of hydrocarbon products by adjusting the active center of the catalyst and controlling the reaction conditions, which is beneficial to the green and low-carbon mining of heavy oil by utilizing the heat released by chemical reactions and the generation of hydrocarbons, and is beneficial to the integrated development of upstream and downstream industries.

[0071] In the present invention, the molar ratio of the raw gases CO and H2 can be 1:(0.1-10), and can be further preferably 1:(0.3-5). Typical but non-limiting molar ratios are, for example, 1:0.3, 1:0.5, 1:1, 1:2, 1:3, 1:4, and 1:5.

[0072] In the present invention, the amount of catalyst and the mass space velocity of the raw gas can be 100h -1 ~30000h -1 , which may be further preferably 1000h -1 ~20000h -1 , with a typical but non-limiting mass space velocity of, for example, 1000 h -1 、2000h -1 、3000h -1 , 4000h -1 , 5000h -1 、6000h -1 、7000h -1 、8000h -1 , 9000h -1 、10000h -1 、15000h -1 、20000h -1 、25000h -1 、30000h -1 .

[0073] The reaction temperature of the simulated underground heavy oil reservoir reactor can be 200°C to 400°C, and typical but non-limiting temperatures are, for example, 200°C, 220°C, 240°C, 260°C, 280°C, 300°C, 320°C, 340°C, 360°C, 380°C, and 400°C; the reaction pressure can be 1Mpa to 5Mpa, and typical but non-limiting pressures are, for example, 1Mpa, 1.5Mpa, 2Mpa, 2.5Mpa, 3Mpa, 3.5Mpa, 4Mpa, 4.5Mpa, and 5Mpa.

[0074] In the present invention, the reaction heat release can be 10KJ / Nm 3 ~1000KJ / Nm 3 , which can increase the recovery of heavy oil by 1% to 10%. Its typical but non-limiting heat release is, for example, 10KJ / Nm 3 、50KJ / Nm 3 、100KJ / Nm 3 、200KJ / Nm 3 、300KJ / Nm 3 、400KJ / Nm 3 、500KJ / Nm 3 、600KJ / Nm3 、700KJ / Nm 3 、800KJ / Nm 3 、900KJ / Nm 3 、1000KJ / Nm 3 The generated product distribution includes at least one of methane, light alkanes, olefins, naphtha components, diesel components and gasoline components.

[0075] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0076] Example 1

[0077] A preparation method of a FeM@N core-shell catalyst, designated as Cat-1 catalyst (K-FeZn@ZSM-5, wherein the mass ratio of Fe2O3 to ZnO is 70:30), comprises the following steps:

[0078] 14.1 g of ferric nitrate nonahydrate and 8.9 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0079] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0080] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain solution D; K-FeZn particles and solution D were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@ZSM-5 core-shell catalyst.

[0081] Example 2

[0082] A preparation method of a FeM@N core-shell catalyst, designated as Cat-2 catalyst (K-FeZn@ZSM-5, wherein the mass ratio of Fe2O3 to ZnO is 80:20), comprises the following steps:

[0083] 16.2 g of ferric nitrate nine hydrate and 5.95 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0084] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0085] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain solution D; K-FeZn particles and solution D were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@ZSM-5 core-shell catalyst.

[0086] Example 3

[0087] A preparation method of a FeM@N core-shell catalyst, designated as Cat-3 catalyst (K-FeZn@ZSM-5, wherein the mass ratio of Fe2O3 to ZnO is 90:10), comprises the following steps:

[0088] 18.2 g of ferric nitrate nonahydrate and 2.98 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0089] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0090] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain solution D; K-FeZn particles and solution D were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@ZSM-5 core-shell catalyst.

[0091] Example 4

[0092] A preparation method of a FeM@N core-shell catalyst, designated as Cat-4 catalyst (K-FeZn@β, wherein the mass ratio of Fe2O3 to ZnO is 90:10), comprises the following steps:

[0093] 18.2 g of ferric nitrate nonahydrate and 2.98 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0094] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0095] Tetraethylammonium hydroxide, silicon dioxide, aluminum oxide and solvent were mixed in a molar ratio of 0.35:1:0.04:40, and stirred at room temperature for 4 hours to obtain a D solution; K-FeZn particles and D solution were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 150°C, a hydrothermal time of 72 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@β core-shell catalyst.

[0096] Example 5

[0097] A preparation method of a FeM@N core-shell catalyst, designated as Cat-5 catalyst (K-FeZn@SiO2, wherein the mass ratio of Fe2O3 to ZnO is 90:10), comprises the following steps:

[0098] 18.2 g of ferric nitrate nonahydrate and 2.98 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0099] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0100] Hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:35 to prepare solution D, and then K-FeZn particles were added to solution D and stirred at room temperature for 4-6 hours. The solid was then filtered out, washed 5 times until neutral, and then dried in an oven, and then calcined at 400°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@SiO2 core-shell catalyst.

[0101] Example 6

[0102] A preparation method of a FeM@N core-shell catalyst, designated as Cat-6 catalyst (K-FeZn@Silicalite-1, wherein the mass ratio of Fe2O3 to ZnO is 90:10), comprises the following steps:

[0103] 18.2 g of ferric nitrate nonahydrate and 2.98 g of zinc nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeZn catalyst;

[0104] 10g of FeZn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeZn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeZn catalyst;

[0105] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, ethanol and water were mixed in a molar ratio of 0.35:1:0.1:25, and stirred at room temperature for 4 hours to obtain solution D; K-FeZn particles and solution D were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 400°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeZn@Silicate-1 core-shell catalyst.

[0106] Example 7

[0107] A preparation method of a FeM@N core-shell catalyst, designated as Cat-7 catalyst (K-FeMg@ZSM-5, wherein the mass ratio of Fe2O3 to MgO is 90:10), comprises the following steps:

[0108] 18.2 g of ferric nitrate nonahydrate and 2.98 g of magnesium nitrate hexahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then placed in an oven to dry, and then calcined at 400° C. in air for 12 hours to obtain a FeMg catalyst;

[0109] 10g of FeMg powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeMg powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into tablets with a size of 40-60 mesh to obtain a K-FeMg catalyst;

[0110] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain solution D; K-FeMg particles and solution D were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeMg@ZSM-5 core-shell catalyst.

[0111] Example 8

[0112] A preparation method of a FeM@N core-shell catalyst, designated as Cat-8 catalyst (K-FeMn@ZSM-5, wherein the mass ratio of Fe2O3 to MnO is 90:10), comprises the following steps:

[0113] 18.2 g of ferric nitrate nine hydrate and 2.51 g of manganese nitrate tetrahydrate were weighed and dissolved in 240 ml of deionized water to prepare solution A; 10.6 g of sodium carbonate was weighed and dissolved in 100 ml of deionized water to prepare solution B; under a reaction temperature of 60° C. and mechanical stirring, a co-current co-precipitation method was used to drop solution A and solution B into a beaker with 50 ml of deionized water for precipitation, and the pH value was controlled at 8.5 to form a precipitate, which was aged for 3 hours; the precipitate was filtered, washed with deionized water for 3-5 times until neutral, then dried in an oven, and then calcined at 400° C. in air for 12 hours to obtain a FeMn catalyst;

[0114] 10g of FeMn powder was placed in a beaker, and 1.0g of potassium nitrate was weighed and dissolved in 10ml of deionized water to prepare a C solution; an equal volume of the C solution was impregnated into the FeMn powder, and then placed in a 120°C oven for drying, and then calcined in air at 400°C for 12h, and crushed into 40-60 mesh tablets to obtain a K-FeMn catalyst;

[0115] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain a D solution; the K-FeMn granules and the D solution were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a K-FeMn@ZSM-5 core-shell catalyst.

[0116] Example 9

[0117] A preparation method of a FeM@N core-shell catalyst, designated as Cat-9 catalyst (Na-FeMg@ZSM-5, wherein the mass ratio of Fe2O3 to MgO is 90:10), comprises the following steps:

[0118] Weigh 18.1g of ferric nitrate nonahydrate and 2.56g of magnesium nitrate hexahydrate and dissolve them in 240ml of deionized water to prepare solution A; weigh 10.6g of sodium carbonate and dissolve them in 100ml of deionized water to prepare solution B; under a reaction temperature of 60°C and mechanical stirring, use a co-current co-precipitation method to drop solution A and solution B into a beaker with 50ml of deionized water for precipitation, control the pH value at 8.5, form a precipitate, and age for 3h; filter the precipitate, wash it with deionized water 1-2 times, then place it in an oven to dry, and then roast it in air at 400°C for 12h, press it into tablets and crush it into 40-60 meshes to prepare a Na-FeMg catalyst;

[0119] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain a D solution; the Na-FeMg granules and the D solution were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and vented, filtered, washed 5 times until neutral, and then dried in an oven, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain a Na-FeMg@ZSM-5 core-shell catalyst.

[0120] Example 10

[0121] A FeM@N core-shell catalyst is designated as Cat-10 catalyst (Na-FeZn@ZSM-5 2L , wherein the mass ratio of Fe2O3 to ZnO is 90:10), comprising the following steps:

[0122] Weigh 18.1g of ferric nitrate nonahydrate and 2.98g of zinc nitrate hexahydrate and dissolve them in 240ml of deionized water to prepare solution A; weigh 10.6g of sodium carbonate and dissolve them in 100ml of deionized water to prepare solution B; under a reaction temperature of 60°C and mechanical stirring, use a co-current co-precipitation method to drop solution A and solution B into a beaker with 50ml of deionized water for precipitation, control the pH value at 8.5, form a precipitate, and age for 3h; filter the precipitate, wash it with deionized water 1-2 times to neutrality, then place it in an oven to dry, and then roast it in air at 400°C for 12h, press it into tablets and crush it into 40-60 meshes to prepare a Na-FeZn catalyst;

[0123] Tetrapropylammonium hydroxide, tetraethyl orthosilicate, aluminum nitrate, ethanol and water were mixed in a molar ratio of 0.35:1:0.01:0.1:25, and stirred at room temperature for 4 hours to obtain a D solution; the Na-FeZn granules and the D solution were simultaneously transferred into a crystallization kettle for hydrothermal treatment at a hydrothermal temperature of 180°C, a hydrothermal time of 18 hours, and a rotation speed of 2 r / min. After the hydrothermal treatment, the solid was cooled and emptied, filtered, washed 5 times until neutral, and then dried in an oven, and the above steps were repeated once, and then calcined at 550°C in air for 6 hours with a heating rate of 1°C / min to obtain Na-FeZn@ZSM-5. 2L Core-shell catalyst.

[0124] Test Example 1

[0125] A 5 ml fixed bed reactor was used, the catalyst loading amount was 1.0 g, diluted with 2.0 g fine quartz sand, the reducing atmosphere was 50% H2-50% CO, the flow rate was 100 ml / min, the reduction temperature was 350°C, and the reduction time was 8 h; after the reduction process was completed, the temperature was lowered to room temperature, and the reaction system was purged with raw gas (H2 / CO=2.0) for 0.5 h, and the pressure was pushed to 1.0 MPa with raw gas, the reaction temperature was 280°C, and the raw gas space velocity was 2000 h -1 , the raw gas composition H2 / CO=2.0, the reaction started after the temperature and pressure were stable, and the reaction tail gas products were analyzed by two online chromatographs and one offline chromatograph. The inorganic gas tail gas analysis conditions were: the chromatographic column was activated carbon, the column temperature was 80℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was a thermal conductivity cell detector; the gas phase organic product analysis conditions were: the chromatographic column was HP-PLOTQ, the column temperature program was raised to 220℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was an ion flame detector; the heavy component liquid phase product was collected by a cold trap, and after being taken out, it was analyzed by offline chromatography. The analysis conditions were: the chromatographic column was Porapak-T, the column temperature program was raised to 270℃, the carrier gas was hydrogen, and the flow rate was 30ml / min. The evaluation results of the catalyst are shown in Table 1.

[0126] Table 1 Catalyst performance

[0127] catalyst CO conversion rate (%) C5-C12 selectivity (%) Temperature rise(℃) Cat-1 68.2 37.3 39 Cat-2 78.5 41.6 65 Cat-3 88.3 50.6 135 Cat-4 77.3 32.1 62 Cat-5 71.5 52.5 56 Cat-6 76.1 42.8 61 Cat-7 83.7 45.9 67 Cat-8 89.2 38.2 73 Cat-9 85.7 46.9 78 Cat-10 84.5 54.0 89

[0128] Test Example 2

[0129] A 5ml fixed bed reactor was used, the catalyst was Cat-3 catalyst, the catalyst loading was 1.0g, diluted with 2.0g fine quartz sand, the reducing atmosphere was 50% H2-50% CO, the flow rate was 100ml / min, the reduction temperature was 350°C, and the reduction time was 8h; after the reduction process was completed, the temperature was lowered to room temperature, and the reaction system was purged with raw gas (H2 / CO=2.0) for 0.5h, and the pressure was rushed to 1.0MPa with raw gas, and different reaction temperatures were investigated, and the raw gas space velocity was 2000h -1, the raw gas composition H2 / CO=2.0, the reaction started after the temperature and pressure were stable, and the reaction tail gas products were analyzed by two online chromatographs and one offline chromatograph. The analysis conditions of inorganic gas tail gas were: the chromatographic column was activated carbon, the column temperature was 80℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was a thermal conductivity cell detector; the analysis conditions of gas phase products were: the chromatographic column was HP-PLOTQ, the column temperature program was raised to 220℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was an ion flame detector; the liquid phase products of the heavy components were collected by a cold trap, taken out and analyzed by chromatography, and the analysis conditions were: the chromatographic column was Porapak-T, the column temperature program was raised to 270℃, the carrier gas was hydrogen, and the flow rate was 30ml / min. The evaluation results of different reaction temperatures of the catalyst are shown in Table 2.

[0130] Table 2 Performance of Cat-3 catalyst at different temperatures

[0131] Temperature(℃) CO conversion rate (%) C5-C12 selectivity (%) Temperature rise(℃) 260 71.6 43.2 85 280 88.3 50.6 135 300 92.3 49.8 142 320 95.3 42.3 156 340 95.7 37.4 160

[0132] Test Example 3

[0133] A 5ml fixed bed reactor was used, the catalyst was Cat-3 catalyst, the catalyst loading was 1.0g, diluted with 2.0g fine quartz sand, the reducing atmosphere was 50% H2-50% CO, the flow rate was 100ml / min, the reduction temperature was 350°C, and the reduction time was 8h; after the reduction process was completed, the temperature was lowered to room temperature, and the reaction system was purged with raw gas (H2 / CO=2.0) for 0.5h, and the pressure was rushed to 1.0MPa with raw gas, and different reaction pressures were investigated, and the raw gas space velocity was 2000h -1 , the raw gas composition H2 / CO=2.0, the reaction started after the temperature and pressure were stable, and the reaction tail gas products were analyzed by two online chromatographs and one offline chromatograph. The online analysis conditions of inorganic gas tail gas were: the chromatographic column was activated carbon, the column temperature was 80℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was a thermal conductivity cell detector; the gas phase product analysis conditions were: the chromatographic column was HP-PLOT Q, the column temperature program was raised to 220℃, the carrier gas was hydrogen, the flow rate was 50ml / min, and the detector was an ion flame detector; the heavy component liquid phase product was collected by a cold trap, and after being taken out, it was analyzed by chromatography. The analysis conditions were: the chromatographic column was Porapak-T, the column temperature program was raised to 270℃, the carrier gas was hydrogen, and the flow rate was 30ml / min. The evaluation results of different reaction pressures of the catalyst are shown in Table 3.

[0134] Table 3 Performance of Cat-3 catalyst at different pressures

[0135] Pressure / MPa CO conversion rate (%) C5-C12 selectivity (%) Temperature rise(℃) 0.1 32.1 22.5 40 1 88.3 50.6 135 2 92.4 46.9 140 3 93.5 39.4 132

[0136] In summary, the preparation method of the FeM@N core-shell catalyst of the present invention is simple to operate and has broad application prospects. The obtained FeM@N core-shell catalyst is suitable for simulating exothermic reactions under high temperature and high pressure environments under underground heavy oil layers, and has high syngas conversion rate, controllable product distribution and heat release. The promotion of this catalyst is conducive to the integrated development of upstream and downstream, and the use of chemical reaction heat release and hydrocarbon generation can provide a new technical route for green and low-carbon heavy oil mining.

[0137] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A FeM@N core-shell catalyst, characterized in that: It includes an iron-based catalyst as a core and an inorganic membrane as a shell; The inorganic membrane has a mesoporous and / or microporous structure; The inorganic film includes at least one of SiO2, ZSM-5, β and Silicalite-1.

2. The FeM@N core-shell catalyst according to claim 1, characterized in that The particle size of the iron-based catalyst as the core is 20nm-2000nm, preferably 50nm-1000nm; The thickness of the inorganic film as the shell layer is 1 nm-500 nm, preferably 20 nm-200 nm.

3. A method for preparing the FeM@N core-shell catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (a) subjecting a metal precursor solution to a coprecipitation reaction in an alkaline environment to obtain a precipitate, and calcining the precipitate to obtain a catalyst containing an iron-based metal; (b) In-situ coating of the iron-based metal catalyst by an inorganic membrane, followed by aging and crystallization, to obtain the FeM@N core-shell catalyst.

4. The preparation method according to claim 3, characterized in that: The metal precursor includes iron salt and metal additive; The iron salt includes at least one of ferric nitrate, ferric chloride, ferric sulfate and ferric bromide; The metal additive includes at least one of Zr salt, Mn salt, Ce salt, Zn salt, K salt, Na salt and La salt; The molar ratio of the iron salt to the metal additive is 1:(0.01-5), preferably 1:(0.1-1).

5. The preparation method according to claim 4, characterized in that: The molar concentration of the metal precursor solution is 0.1 mol / L to 10 mol / L, preferably 0.5 mol / L to 2 mol / L; The molar concentration of the alkaline solution in the alkaline environment is 0.1 mol / L to 10 mol / L, preferably 0.5 mol / L to 2 mol / L.

6. The preparation method according to claim 3, characterized in that: The coprecipitation reaction temperature is 50°C to 120°C, preferably 70°C to 90°C; The pH condition of the coprecipitation reaction is 7-12, preferably 7.5-10.

7. The preparation method according to claim 3, characterized in that: The roasting method includes roasting in air; The calcination temperature is 300°C to 600°C, preferably 400°C to 500°C; The calcination time is 10 h to 24 h, preferably 15 h to 18 h.

8. The preparation method according to claim 3, characterized in that: The in-situ coating method includes at least one of a sol-gel method, a hydrothermal synthesis method and a physical coating method.

9. The preparation method according to claim 3, characterized in that: The aging temperature is 25°C to 100°C, preferably 30°C to 60°C; The crystallization temperature is 60°C to 240°C, preferably 130°C to 180°C; The method further comprises the step of calcining the obtained product in air after the crystallization.

10. Use of the FeM@N core-shell catalyst according to claim 1 or 2 in in-situ hydrocarbon generation and heat release during thermal recovery of heavy oil.

Citation Information

Patent Citations

  • In-situ thickened oil catalytic reforming metal nanocrystalline viscosity reducer and preparation method thereof

    CN107880866A

  • Experimental device and method for simulating action of multidimensional chemical reaction on porous medium

    CN114658403A

  • Method for exploiting heavy oil reservoir by utilizing shaft catalytic heat generation

    CN114876429A